Assessing organizational innovativeness – evidence from corporate narratives. (5th October 2015) - Ackermann, Malte Stefan; Stephan, Michael; Penrose, John M.
Abstract : Purpose: – The purpose of this paper is twofold: to quantify the communication of organizational innovativeness (OI) on a large scale; and to examine the relationship of communicating OI and the corresponding investments in research and development (R & D) of multinational corporations (MNCs). Design/methodology/approach: – In total, 3, 043 annual reports from 326 MNCs are examined utilizing quantitative content analysis, which focusses on fixed selected terminologies, in the years 1998-2008. Findings: – Scholars assume that the capacity for OI is becoming the single most important task in organizational survival. Even though in the sample the investments in R & D are not increasing, even slightly declining, the communication of OI is increasing. Using mixed-effects regression analysis, the findings indicate that the corporations that are investing in R & D are also communicating these efforts correspondingly. Practical implications: – This is the first study that measures the communication of OI using quantitative content analysis. Originality/value: – The results indicate that not only do the communication efforts of an organization's OI have a perceived increasing importance. They also suggest that OI itself has become more important for organizations from a strategic point of view.